Rear seating position is associated with a higher risk of mortality in motor vehicle crashes: analysis of Japanese Trauma Data Bank. Issue 1 (15th July 2019) - Okada, Nobunaga; Matsuyama, Tasuku; Takebe, Kotaro; Kitamura, Tetsuhisa; Sado, Junya; Ohta, Bon
Abstract : Aim: The study examined the association of vehicle seating positions with the risk of death in serious motor vehicle crashes (MVCs) in Japan. Methods: Data from the Japan Trauma Data Bank between 2004 and 2015 were analyzed. All MVC drivers with the legal age for driving and all copassengers were enrolled ( n  = 23, 040). The cases were divided into three groups based on their seating position during the crash: the driver seat, front passenger seat, and rear passenger seats. The primary outcome variable was in‐hospital mortality. Multivariable logistic regression analysis was used to assess the association between the seating position and in‐hospital mortality. Potential factors associated with each seating position and in‐hospital mortality were also assessed. Results: The odds ratios (ORs) for deaths were estimated for front and rear passengers compared to those for the driver in MVCs. The adjusted ORs (95% confidence interval [CI]) for death were 0.96 (0.84–1.11) and 1.22 (1.04–1.42) for front and rear passengers, respectively. Factors significantly associated with MVC deaths were age over 71 years (OR = 3.38; 95% CI, 2.58–4.41), male gender (OR = 1.54; 95% CI, 1.39–1.71), and night driving (OR = 1.17; 95% CI, 1.06–1.29). Conclusions: This hospital‐based study suggested that rear seating increased the risk of MVC‐related death. Further studies are needed in order to find mechanisms of the increase in mortality by the seating position. Abstract : We found that the risk of death is higher in rear seat passengers compared to the driver and front copassenger. The risk of mortality was higher in those who were more than 71 years of age, irrespective of the seating position. Only in the driver seat position, the male group or those motor vehicle crashes that occurred at night time had a significantly higher risk of death.